What makes all-Chinese table tennis matches different from non-Chinese matches? - Foo, Ning Xin (Nanyang Technological University, 2022)
The sport was dominated by the Europeans until the 1950s when the Asian countries, namely China and Japan, entered the World Championships for the first time, which marked a new reign in the world of table tennis. This study aims to use performance analysis to identify the differences in objective temporal and technical game performances between the top-20 ranked female China and non-China athletes, with the goal of improving the standard of table tennis locally. 12 matches between 11 athletes (4 China and 7 non-China) who were right-handed and used the aggressive style of play were analysed. Matches analysed divided into three groups: (i) China vs China (CvC) (ii) China vs non-China (CvNC) (iii) non-China vs non-China (NCvNC). Based on past research, CvC match-ups were hypothesised to have better technical (serving advantage, line-change technique, higher forced errors but lower unforced errors) and temporal results (rally length and intensity) than the other two groups. The findings from this study showed higher temporal results in CvC match-ups, with longer average rally lengths and higher rally intensity. Technical results were only partially conclusive, that China players were less likely to make unforced errors and more likely to make forced errors. No significant differences were found for service advantage and line-changing techniques for all three match-ups between all match-ups. With the negligible differences in terms of service advantage and line changing techniques, it can be concluded that the China players excel mainly due to their skills levels, and less due to the strategic play.